Insulinoma - Ria Yuniarti; Suly Auline (Jurnal RSMH Palembang, 2020)
A B S T R A C TInsulinoma is a functional neuroendocrine neoplasm consisting of insulin-producingcells, which produce insulin uncontrollably, causing a hypoglycemic syndrome. TheHypoglycemic syndrome is a result of hyperinsulinemia which causes adrenergicsymptoms and neuroglycopenia. The clinical diagnosis is based on the Whipple triad,insulin, and C peptide levels in a 72-hour fasting state. Generally, insulinoma is abenign neoplasm with a proliferation index of Ki-67 <2%. On histological features, thegrowth pattern of the insulinoma is usually trabecular or solid. Some insulinomas showa tubuloacinar growth pattern with psammoma bodies. We reported one case ofinsulinoma in a 65-year-old woman, who had experienced fainting, cold sweats for 3years, especially when the patient ate late or at midnight while sleeping. A CT scanshowed a tumor mass in the pancreas possibly an insulinoma and a pancreatectomywas performed. The results of the histopathological examination are bu following peerunder Insulinoma.